Scn2a severe hypomorphic mutation decreases excitatory synaptic input and causes autism-associated behaviors - Wang, Hong-Gang; Bavley, Charlotte C.; Li, Anfei; Jones, Rebecca M.; Hackett, Jonathan E.; Bayleyen, Yared; Lee, Francis S.; Rajadhyaksha, Anjali M.; Pitt, Geoffrey S. (JCI Insight, 2021)
SCN2A, encoding the neuronal voltage-gated Na+ channel NaV1.2, is one of the most commonly affected loci linked to autism spectrum disorders (ASDs). Most ASD-associated mutations in SCN2A are loss-of-function mutations, but studies examining how such mutations affect neuronal function and whether Scn2a mutant mice display ASD endophenotypes have been inconsistent. We generated a protein truncation variant Scn2a mouse model (Scn2aΔ1898/+) by CRISPR that eliminates the NaV1.2 channel's distal intracellular C-terminal domain, and we analyzed the molecular and cellular consequences of this variant in a heterologous expression system, in neuronal culture, in brain slices, and in vivo. We also analyzed multiple behaviors in WT and Scn2aΔ1898/+ mice and correlated behaviors with clinical data obtained in human subjects with SCN2A variants. Expression of the NaV1.2 mutant in a heterologous expression system revealed decreased NaV1.2 channel function, and cultured pyramidal neurons isolated from Scn2aΔ1898/+ forebrain showed correspondingly reduced voltage-gated Na+ channel currents without compensation from other CNS voltage-gated Na+ channels. Na+ currents in inhibitory neurons were unaffected. Consistent with loss of voltage-gated Na+ channel currents, Scn2aΔ1898/+ pyramidal neurons displayed reduced excitability in forebrain neuronal culture and reduced excitatory synaptic input onto the pyramidal neurons in brain slices. Scn2aΔ1898/+ mice displayed several behavioral abnormalities, including abnormal social interactions that reflect behavior observed in humans with ASD and with harboring loss-of-function SCN2A variants. This model and its cellular electrophysiological characterizations provide a framework for tracing how a SCN2A loss-of-function variant leads to cellular defects that result in ASD-associated behaviors.